Analisis Kesejahteraan Petani Padi di Desa Jurangsapi Kecamatan Tapen Kabupaten Bondowoso Sebelum dan Saat Pandemi Covid-19 - Robiatul Adawiyah; Harpowo Harpowo; M. Zul Mazwan (AGRIMOR, 2023)
The occurrence of the Covid-19 pandemic in Indonesia has disrupted the people's economy, especially rice farmers. Large-Scale Social Restrictions (PSBB) certainly have an impact on people's lives, including farmers. This has caused several input prices and the selling price of agricultural products to be different from the situation before the Covid-19 pandemic. One of the food crops that has experienced price changes due to Covid-19 is rice. In addition to the price of agricultural inputs, food and non-food prices have also increased due to the Covid-19 pandemic, so that the costs incurred by farmers have also increased. Changes in price increases of basic needs and agricultural needs will of course also affect the level of welfare of rice farmers so it is necessary to conduct research on the welfare of rice farmers before and during the Covid-19 pandemic when viewed from the income and expenses of the rice farmer's house. The survey method is a research design in this study and the sample purchasing technique uses a purposive sampling technique, namely choosing respondents deliberately by considering many things and the number of respondents is 30 people. The respondents of this study were rice farmers in Jurangsapi Village, Tapen District, Bondowoso Regency. This study uses data analysis in the form of Farmer Exchange Rate (NTP) analysis to determine the level of welfare of rice farmers before and during the Covid-19 pandemic. This research shows that when a pandemic occurred, the Farmer Exchange Rate (NTP) produced was 118%, which meant that there was a surplus because the Farmer's Exchange Rate (NTP) was > 100, while during a pandemic the Farmer's Exchange Rate (NTP) produced fell to 94%, indicating that the welfare of farmers during the occurrence of Covid-19 decreased because the Farmer's Exchange Rate (NTP) was > 100.